Safety of primaquine given to people with G6PD deficiency: systematic review of prospective studies - Uthman, Olalekan A. (Malar J, 2017)
BACKGROUND: Haemolysis risk with single dose or short course primaquine was evaluated in glucose-6-phosphate dehydrogenase (G6PD) deficient people. METHODS: Major electronic databases (to August 2016) were searched for single or short course 8-aminoquinolines (8-AQ) in (1) randomized comparisons against placebo in G6PD deficient people; and (2) observational comparisons in G6PD deficient compared to replete people. Two authors independently assessed eligibility, risk-of-bias, and extracted data. RESULTS: Five randomized controlled trials and four controlled observational cohorts were included. In G6PD deficient individuals, high-dose (0.75 mg/kg) PQ resulted in lower average haemoglobin levels at 7 days (mean difference [MD] −1.45 g/dl, 95% CI −2.17 to −0.74, 2 trials) and larger percentage fall from baseline to day 7 (MD −10.31%, 95% CI −17.69 to −2.92, 3 trials) compared to placebo. In G6PD deficient compared to replete people, average haemoglobin was lower at 7 days (MD −1.19 g/dl, 95% CI −1.94 to −0.44, 2 trials) and haemoglobin change from baseline to day 7 was greater (MD −9.10%, 95% CI −12.55 to −5.65, 5 trials). One small trial evaluated mid-range PQ dose (0.4–0.5 mg/kg) in G6PD deficient people, with no difference detected in average haemoglobin at day 7 compared to placebo. In one cohort comparing G6PD deficient and replete people there was a greater fall with G6PD deficiency (MD −4.99%, 95% CI −9.96 to −0.02). For low-dose PQ (0.1–0.25 mg/kg) in G6PD deficient people, haemoglobin change from baseline was similar to the placebo group (MD 1.72%, 95% CI −1.89 to 5.34, 2 trials). Comparing low dose PQ in G6PD deficient with replete people, the average haemoglobin was lower in the G6PD deficient group at 7 days (−0.57 g (95% CI −0.97 to −0.17, 1 trial)); although change from baseline was similar (MD −1.45%, 95% CI −5.69 to 2.78, 3 trials). CONCLUSIONS: Falls in average haemoglobin are less marked with the 0.1 to 0.25 mg/kg PQ than with the 0.75 mg/kg dose, and severe haemolytic events are not common. However, data were limited and the evidence GRADE was low or very low certainty. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12936-017-1989-3) contains supplementary material, which is available to authorized users.